2005
DOI: 10.1128/jvi.79.7.4219-4228.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Adult Mouse Neurovirulence Determinants of the Sindbis Virus Strain AR86

Abstract: Sindbis virus infection of mice has provided valuable insight into viral and host factors that contribute to virus-induced neurologic disease. In an effort to further define the viral genetic elements that contribute to adult mouse neurovirulence, the neurovirulent Sindbis virus strain AR86 was compared to the closely related (22 single amino acid coding changes and the presence or absence of an 18-amino-acid sequence in nsP3 [positions 386 to 403]) but avirulent Girdwood strain. Initial studies using chimeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
66
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 30 publications
0
66
1
Order By: Relevance
“…However, studies of adult mice have demonstrated that infection with most Sindbis group alphaviruses results in encephalitic disease (11,37). Recent work has demonstrated that Sindbis group alphaviruses, such as S.A.AR86 and TR339, replicated in bone and joint-associated tissues of adult CD-1 mice; however, virus-induced inflammation or other pathology was not observed within these tissues (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of adult mice have demonstrated that infection with most Sindbis group alphaviruses results in encephalitic disease (11,37). Recent work has demonstrated that Sindbis group alphaviruses, such as S.A.AR86 and TR339, replicated in bone and joint-associated tissues of adult CD-1 mice; however, virus-induced inflammation or other pathology was not observed within these tissues (15).…”
Section: Discussionmentioning
confidence: 99%
“…For the Girdwood replicon system, the non-structural coding region of the genome from nucleotides 41-6463 was transferred from the full-length infectious clone pG100 [23] into the AR86-based replicon pREP89 [22], using restriction enzymes MfeI and BstBI. All non-structural coding differences between AR86 and GirdwoodS.A.…”
Section: Replicon Productionmentioning
confidence: 99%
“…(called Girdwood hereafter). In adult mice, a virus derived from the infectious clone of AR86 (S300) causes lethal disease following intracranial inoculation (27,28,58,60), while the closely related Girdwood virus (clone G100) is avirulent, even though both S300 and G100 replicate to similar levels within the CNS of mice at early times postinfection (60). The difference in virulence is mediated by four genetic determinants within AR86, which result in a gain of full virulence when introduced into the avirulent G100 background.…”
mentioning
confidence: 99%